Stress Management: Ways to Cope - Suzanna Smith; Joe Pergola (EDIS, 2003)
Stress management practices help you cope with stress. Coping is what you do to deal with the pressure of stressors and stay steady. Coping is a natural process we do throughout our lives. Some ways of coping are more helpful than others. In this series we talk about the helpful coping strategies. This publication focuses on ways you can think about problems that will help you overcome stress. This document is FCS2078, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, IFAS, University of Florida. First Publication: June 1989 as FCS2081. Reviewed: August 1999. Revised: January 2003.